2021
DOI: 10.1002/cl2.1205
|View full text |Cite
|
Sign up to set email alerts
|

PROTOCOL: Residential energy efficiency interventions: An effectiveness systematic review

Abstract: This review aims to identify, appraise and synthesise the evidence available on the effectiveness of energy efficiency measure installations, including those bundled with behavioural interventions. The synthesis will estimate the overall impact of these interventions as well as examine possible causes of variation in impacts. We will also attempt to assess the cost-effectiveness of residential energy efficiency interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…We excluded 12,879 studies based on the inclusion criteria and 97 studies were identified as potentially relevant studies and underwent a full‐text screening. At the title and abstract screening, most of the studies were excluded because they did not include an intervention (6919), the intervention was not relevant (5015), the study design used was not one of those listed in the protocol (Berretta et al, 2021 ) (515), lack of empirical data (290), or they did not address effectivenss (131); the remaining studies were excluded because they were duplicates. Excluding a large number of the studies initially identified is not unusual.…”
Section: Resultsmentioning
confidence: 99%
“…We excluded 12,879 studies based on the inclusion criteria and 97 studies were identified as potentially relevant studies and underwent a full‐text screening. At the title and abstract screening, most of the studies were excluded because they did not include an intervention (6919), the intervention was not relevant (5015), the study design used was not one of those listed in the protocol (Berretta et al, 2021 ) (515), lack of empirical data (290), or they did not address effectivenss (131); the remaining studies were excluded because they were duplicates. Excluding a large number of the studies initially identified is not unusual.…”
Section: Resultsmentioning
confidence: 99%